The influence of the digital literacy program on msmes as an effort for business resilience in improving the national economy - Shakira, Vera (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to explore the importance of digital literacy for society, especially MSMEs, to encourage a national business resilience program to enhance the national economy concerned by the COVID-19 pandemic. The method used in this research is qualitative research which utilizes official literature sources. The outcomes of this research found that in the digital economy era, consumer caution in choosing goods and services has increased, especially in line with the impact of the COVID-19 pandemic which limits direct consumer activities. It reduces consumer confidence in the products and services offered by Micro, Small, and Medium Enterprises (MSMEs). To overcome this challenge, MSMEs need to improve the quality of their products and increase the types of services offered to consumers, such as product delivery services via online media. Additionally, improvements in service standards, including product cleanliness and effective online communication, are also required to rebuild consumer trust. With improved product and service quality, it is hoped that consumer satisfaction will increase, which in turn will support the recovery and growth of MSME businesses in the future.